2019
DOI: 10.1103/physrevlett.122.084102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Freezing of Relaxation to Equilibrium

Abstract: We provide evidence of an extremely slow thermalization occurring in the Discrete NonLinear Schrödinger (DNLS) model. At variance with many similar processes encountered in statistical mechanics -typically ascribed to the presence of (free) energy barriers -here the slowness has a purely dynamical origin: it is due to the presence of an adiabatic invariant, which freezes the dynamics of a tall breather. Consequently, relaxation proceeds via rare events, where energy is suddenly released towards the background.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 54 publications
4
55
1
Order By: Relevance
“…Below this line no physical state is allowed, while a standard thermal phase extends in between these two lines: dynamics (2) makes any initial state eventually thermalize to energy equipartition. Above the β = 0 line numerical studies (e.g., see [4,6]) have shown that the hamiltonian dynamics of the DNLSE exhibits localized breather excitations. Such excitations can survive over extremely long times (exponentially long in their mass [6]) even in a chain made of a few tens of sites [4].…”
Section: Model and State Of The Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Below this line no physical state is allowed, while a standard thermal phase extends in between these two lines: dynamics (2) makes any initial state eventually thermalize to energy equipartition. Above the β = 0 line numerical studies (e.g., see [4,6]) have shown that the hamiltonian dynamics of the DNLSE exhibits localized breather excitations. Such excitations can survive over extremely long times (exponentially long in their mass [6]) even in a chain made of a few tens of sites [4].…”
Section: Model and State Of The Artmentioning
confidence: 99%
“…Above the β = 0 line numerical studies (e.g., see [4,6]) have shown that the hamiltonian dynamics of the DNLSE exhibits localized breather excitations. Such excitations can survive over extremely long times (exponentially long in their mass [6]) even in a chain made of a few tens of sites [4]. The coupling of the localized breathers among themselves, through the background energy fluctuations, is very weak and their coalescence into a single localized giant breather, even if possible (in fact, breathers are known to merge when they collide [4]), is practically unobservable.…”
Section: Model and State Of The Artmentioning
confidence: 99%
“…Using a recently derived approximation [51] for the integral equation (29), one can also check that the critical exponent for the correlation length coincides with the value from the universality class of the Ising model:…”
Section: Recovery Of Statistical Mechanics For the N = 1 Model: Canonical Averagesmentioning
confidence: 99%
“…Hence we see that our models allow for substantial chaos to be built in at the lattice scale as advertised above. There could be also some adiabatic invariant slowing down the thermalization significantly, as recently investigated in [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect is often observed and, for obvious reasons, we refer to it as localization, ensuring (relative) stability of high energy regions. Recent examples and demonstrations are presented in [10][11][12][13].…”
Section: Diffusive Accelerationmentioning
confidence: 99%